Eksplorasi Konsep Matematika pada Keris dan Pendok - Sholehudin, Muchlis Rifai; Muchlis Rifai; Sri Rejeki; Rini Setyaningsih (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study is to: 1) explore and describe the cultural values contained in keris and pendok; 2) explore and describe the mathematical concepts contained in keris and pendok. This study was a qualitative descriptive study using an ethnographic approach. Data collection was conducted through observation, documentation, and interviews with one cultural expert and one mathematician. The objects of this study were keris and pendok in the Surakarta Keris Museum. The data analysis technique was carried out by categorizing the findings of cultural values and mathematical concepts in each keris and pendok, then processed in three stages: data reduction, data presentation, and conclusion drawing. The results of this study indicate that each keris and pendok blade has its own cultural value in the form of different meanings and philosophies based on the curves of the keris blade and the motifs found on the pendok. Based on the exploration of the curves of the Jangkung, Parungsari, and Nagasiluman keris, there are concepts of odd numbers and trigonometry. Furthermore, the geometric concept of transformation in the form of reflection and dilation is found in the pendok Blewah with the Ulir motif, the Bunton with the Slorok motif, and the Bunton with the Krawang motif. The results of this study are expected to enrich school mathematics learning through the integration of ethnomathematics with the cultural context of the keris and pendok.